Penyuluhan Dan Safari Keluarga Berencana Dalam Meningkatakan Penggunaan KB Implan Dan Iud Di Klinik Pratama Elvi Diana Kecamatan Medan Johor, Kota Medan Tahun 2024 - Asnita Sinaga; Kamelia Sinaga; Rumondang Sitorus; Imran Saputra Surbakti; Melia Ningsih; YunisaAmsah (Compromise Journal Community Proffesional Service Journal, 2024)
Background: Uncontrolled population growth will have many negative impacts. The central government and regional governments have made efforts to reduce the large population growth rate. The government's efforts include socializing two children through the Family Planning program. Intrauterine Device (IUD) is a contraceptive device that is good for women. This tool is very effective and does not need to be remembered every day like birth control pills and birth control injections every month or every three months. For mothers who breastfeed, the IUD does not affect breast milk, the flow or level of breast milk (ASI). Meanwhile, an implant is a type of contraception in the form of an implant made from a type of silastic rubber containing hormones, installed in the upper arm. The implant can be used for a long term of 5 years and is reversible. The advantages of contraception are high effectiveness, implant failure rate, 1 per 100 women per year in the first 5 years, low user failure, once installed there is no need to remember anything. The implant contains levonorgestrel which is a progesterone hormone (Hasliana, 2020). The aim of this community service program (PKM) is to increase the use of implant contraception and IUD contraception at the Pratama Elvi Diana Clinic in 2024. The method used is that counseling on targets is carried out orally. The results are based on the results of the service implementation. Participants in this activity were PUS who visited the Pratama Elvi Diana Clinic totaling 42 people.